2018
DOI: 10.3802/jgo.2018.29.e68
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surgeon volume on outcomes after pelvic exenteration for a gynecologic cancer

Abstract: ObjectiveTo determine the effect of surgeon experience on intraoperative, postoperative and long-term outcomes among patients undergoing pelvic exenteration for gynecologic cancer.MethodsThis was a retrospective analysis of all women who underwent exenteration for a gynecologic malignancy at MD Anderson Cancer Center, between January 1993 and June 2013. A logistic regression was used to model the relationship between surgeon experience (measured as the number of exenteration cases performed by the surgeon prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Other complications included sepsis, thromboembolism, cardiac failure, shock, fistula, and abscess [13]. In a study by Jalloul et al, the types of complications most frequently seen were wound dehiscence (about 55% of cases), urostomy complication, and abscess [11]. In our study, we observed a similar profile of postoperative complications; the most frequently seen were wound complications, and as many as 19% treated due to cancer recurrence required surgical reintervention.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Other complications included sepsis, thromboembolism, cardiac failure, shock, fistula, and abscess [13]. In a study by Jalloul et al, the types of complications most frequently seen were wound dehiscence (about 55% of cases), urostomy complication, and abscess [11]. In our study, we observed a similar profile of postoperative complications; the most frequently seen were wound complications, and as many as 19% treated due to cancer recurrence required surgical reintervention.…”
Section: Discussionsupporting
confidence: 78%
“…To increase the overall number of patients, many previous studies have included cases of PE for other types of pelvic malignancies (for example, rectal and ovarian cancers). This practice may be acceptable for reporting early surgical outcomes, but not for analyzing long-term prognostic factors [3,11]. In our study, we found a correlation between tumor histopathological type and the presence of vaginal fistula with long-term outcomes in cervical cancer patients following PE for cancer recurrence.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The impact of volume on PES outcomes has been previously reported. In an analysis of 167 exenterations performed by 19 surgeons for gynaecological malignancies at a single institution, higher individual surgeon volume was associated with an improvement in perioperative outcomes such as estimated blood loss, transfusion rates, and length of stay . However, this was assessed as a continuous variable and cutoffs for high versus low‐volume were not defined.…”
Section: Discussionmentioning
confidence: 99%